Implementation of Interactive Digital Marketing with the 7P Marketing Concept to Increase Customer Interest on Fly Ash and Bottom Ash Products at PT PJB UP Paiton - Alfiansyah Syam Hidayatullah; Trismawati Trismawati; Yustina Suhandini Tjahjaningsih (Universitas Muhammadiyah Sidoarjo, 2022)
This research was conducted to find out the results that customers are interested in before and after the implementation of conventional marketing and digital marketing methods for fly ash and bottom ash products at PT PJB UP Paiton. The method used in this study is quantitative with a validity test and simple linear regression analysis which is supported by the results of the SPSS experiment. The results of this study indicate that the factors that influence digital marketing customer interest at PT PJB UP Paiton are promotion factors through social media and the application of the 7P Marketing concept namely price, promotion, place, people, and physical evidence which have a positive and significant effect. Now by implementing promotions through social media, PT PJB UP Paiton spends not so much money and gets quite a lot of customer interest and a wide reach.